Karakteristik Sensori dan Fisikokimia Kukis dari Campuran Tepung Mocaf dan Tepung Kulit Buah Naga - Adelina, Nadya Mara; Giovani, Sarah; Jameelah, Maryam; Rosianajayanti, Rosianajayanti; Assagaf, Syarifah Fatimah Zahra (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2024)
To support the goal of zero waste outlined in the sustainable development goals (SDGs), repurposing dragon fruit peel waste presents a promising opportunity. In Indonesia, the high demand for dragon fruit leads to the generation of considerable organic waste. This study explored the use of dragon fruit peel flour, combined with modified cassava (mocaf) flour, as a wheat flour alternative to improve the sensory and chemical properties of gluten-free cookies. The research involved preparing the flours and cookies, followed by conducting sensory, physical, and chemical analyses. A completely randomized design (CRD) was employed, testing five formulations with varying ratios of mocaf flour to dragon fruit peel flour. The results indicated that 73% of panelists preferred the crispiness of cookies containing 25% dragon fruit peel flour, while 60% were satisfied with the color of cookies containing 45% dragon fruit peel flour. Physical analysis showed no significant differences in thickness or bake loss, but there were notable differences in diameter, spread ratio, and color. As the proportion of dragon fruit peel flour increased, the cookies showed significant improvements in chemical characteristics, including higher levels of moisture, ash, fat, protein, and fiber content. Additionally, the content of total phenolics and antioxidant activity increased with higher ratios of dragon fruit peel flour, reaching 1.14 mg GAE/g for total phenolics and 662.64 mg AAE/g for antioxidant activity. FTIR analysis revealed a consistent absorbance pattern across samples, with minor variations in peak intensities at specific wavenumbers. Based on the sensory, physical, and chemical evaluations, cookies containing 45% dragon fruit peel flour were recommended for production.